Azospirillum brasilense and Solarized Manure on the Production and Phytochemical Quality of Tomato Fruits (Solanum lycopersicum L.) - Andrade-Sifuentes, Alfonso; Fortis-Hernández, Manuel; Preciado-Rangel, Pablo; Orozco-Vidal, Jorge Arnaldo; Yescas-Coronado, Pablo; Rueda-Puente, Edgar Omar (Agronomy (Basel), 2020)
Tomato is a vegetable crop with probiotic interest. Currently subject to a global biosecurity emergency due to the epidemic caused by COVID-19, humanity is seeking to maintain its health and become stronger by eating vegetables that have probiotic properties. Considering the request of tomato farmers in the Comarca Lagunera (CL) region, the objective of this work consisted of determining the impact of bioinoculation with Azospirillum brasilense (Ab) and solarized manure (M) on the yield and phytochemical quality of tomato fruits produced in shade mesh. Seeds of the saladette variety TOP 2299 were inoculated with Ab at 1 × 108 CFU.mL. Before 46 days after being sowed, seedlings were transplanted in soil enriched with manure solarized at a rate of 0, 40, 80, 120 and 160 t ha−1; a chemical fertilization (CHF) treatment was also adopted (366-95-635). Emergence, growth, root length, bromatological studies (protein and lipids in plant), yield and organoleptic (Vit C, phenols, flavonoids and lycopene) variables were considered. The results show that biofertilization based on Ab + M40 can be an alternative to produce tomato in shade-house conditions in the CL compared with non-inoculated and CHF treatments.